Pelatihan Membuat Media Pembelajaran Digital - Sandha Soemantri (Universitas Muhammadiyah Surabaya, 2019)
Muhammadiyah University of Surabaya (UMSurabaya) responded to the development of the 4.0 industrial revolution by developing e-learning starting in the odd semester of the 2018/2019 academic year. This matter gives a big impact on the lecture system for the academic community. The Teaching and Education Faculty (FKIP) UMSurabaya as a faculty that prints millennial era teacher candidates responded well by making training to make digital learning media intended for all lecturers. The training was followed by 60 lecturers from FKIP UMSurabaya with the help of ms Office Powerpoint, Fastone, and Filmora software. The method used is the presentation (lecture) and direct practice to produce digital learning media desired by each participant.